DIGITAL VIDEO RECORDED SPEECH TASK BASED PROJECTS TO ENHANCE EFL STUDENTS’ SELF-CONFIDENCE - Qomaruddin, Ahmad Qomaruddin (Journal of English Teaching and Learning, 2023)
This study was intended to improve students’ self-confidence in speaking at one of Islamic secondary school based in Banyuwangi, East Java, Indonesia by applying digital video recording task based projects. This classroom action research was conducted in one cycle. Each cycle comprised four meetings. In this cycle consisted of planning, implementing, observing and reflecting (Kemmis and McTaggrart, 1999). The participants of this study were 34 students of ninth grade. There were three data collection tools of this study. They were teaching scenario, test and field note. The data were analyzed by using descriptive statistics to know the mean and standard deviation. The result of this study showed that the students’ self-confidence improve when they were taught using digital video recording task based projects. It was indicated by the improvement that 82.35% students are confident that it was initially only 47.05% students. The use of digital video recording task based project in teaching speaking could make the teaching and learning process run interactively and the result suggest that the use of digital video recording task based projects are effective to improve the students’ self-confidence. Based on the findings of the study, the English teacher are suggested to use digital video recording task based projects in teaching speaking in order to make the students interested to practice speaking English.